Structure identification of uncertain dynamical networks coupled with complex‐variable chaotic systems. Issue 9 (1st June 2013) - Wu, Zhaoyan; Fu, Xinchu
Abstract : Topological structures and node dynamics of dynamical networks have important influence on their dynamical behaviours. In practical applications, not all of them can be well determined beforehand; therefore this study investigates the structure identification of an uncertain dynamical network coupled with complex‐variable chaotic systems. Based on the Barbalat's lemma, corresponding network estimators are designed for identifying the unknown or uncertain topological structure and node dynamics. Notably, the node dynamics need not to be identical and the topological structure need not to be symmetric or irreducible. Furthermore, this method can also better monitor the switching topological structure of a dynamical network. Numerical simulations are provided to verify the correctness and effectiveness of the theoretical results.